PERANAN RASIO LIKUIDITAS, SOLVABILITAS, RENTABILITAS TERHADAP KINERJA KEUANGAN PADA K.I.A TOUR & TRAVEL JAKARTA - sabil, sabil (Universitas Bina Sarana Informatika, 2016)
Economic development so quickly make the public more critical thinking to follow the development of the information economy. The information economy is the most appropriate use of financial information. The financial statements present the financial position and performance of the company in generating profits. The aim is to give an overview of weakness and financial capability, from year to year, which is to determine the level of liquidity, solvency, profitability, business stability, and the level of risk or the health of a company. For investors it will look at the ratio of the use of the most appropriate to the analysis to be performed. If these ratios do not represent the purpose of the analysis will he do then the ratio will not be used, because the financial concept known as the flexibility, meaning that the formula or various forms of formulas to be adapted to the cases studied. So to assess the financial condition and performance of companies can use ratio is a comparison of the figures contained in the financial statement items. Based on the research results, the company's profit decreased and increased from year to year. The profits to be the absolute size of the company's financial performance or not. Therefore, it is necessary and important to be analyzed by using the ratio of liquidity, solvency, and profitability to measure the performance of the company in order to obtain more accurate results. Keywords: Liquidity, Solvency, Profitability, Financial Performance